Encouraging Teenagers to Improve Speaking Skills through Games in a Colombian Public School - William Urrutia León; Esperanza Vega Cely (Profile: Issues in Teachers' Professional Development)
Our project was implemented with tenth grade students of a public school located in the Usme Zone in Bogotá. We decided to develop this action research project because we were concerned about our students' difficulties when attempting to speak English. They felt inhibited with activities that involved oral interaction mainly because they were afraid of criticism and jokes about what they said. To develop our project we used video recordings, the teacher's journal and questionnaires answered by the students. The results showed that students felt better, free and confident when they participated in oral tasks, particularly during games. We saw collaboration, solidarity and interaction among them. In addition, they were relaxed and happy at the time they had to perform in small groups.